Basaltic feeder dykes in rift zones: geometry, emplacement, and effusion rates - I. Galindo; A. Gudmundsson (Natural Hazards and Earth System Sciences, 2012)
Most volcanic hazards depend on an injected dyke reaching the surface to form a feeder. Assessing the volcanic hazard in an area is thus related to understanding the condition for the formation of a feeder dyke in that area. For this latter, we need good field data on feeder dykes, their geometries, internal structures, and other characteristics that distinguish them from non-feeders. Unfortunately, feeder dykes are rarely observed, partly because they are commonly covered by their own products. For this reason, outcrops are scarce and usually restricted to cliffs, ravines, and man-made outcrops. Here we report the results of a study of feeder dykes in Tenerife (Canary Islands, Spain) and Iceland, focusing on their field characteristics and how their propagation is affected by existing structures. Although Holocene fissure eruptions have been common in both islands, only eleven basaltic feeder dykes have been identified: eight in Tenerife and three in Iceland. They are all well preserved and the relation with the eruptive fissure and/or the deposits is well exposed. While the eruptive fissures are generally longer in Iceland than in Tenerife, their feeders show many similarities, the main ones being that the feeder dykes (1) are generally sheet-shaped; (2) are segmented (as are the associated volcanic fissures); (3) normally contain elongated (prolate ellipsoidal) cavities in their central, topmost parts, that is, 2–3 m below the surface (with solidified magma drops on the cavity walls); (4) contain vesicles which increase in size and number close to the surface; (5) sometimes inject oblique dyke fingers into the planes of existing faults that cross the dyke paths; and (6) may reactivate, that is, trigger slip on existing faults. We analyse theoretically the feeder dyke of the 1991 Hekla eruption in Iceland. Our results indicate that during the initial peak in the effusion rate the opening (aperture) of the feeder dyke was as wide as 0.77 m, but quickly decreased to about 0.56 m. During the subsequent decline in the effusion rate to a minimum, the aperture decreased to about 0.19 m. At a later abrupt increase in the effusion rate, the feeder-dyke opening may have increased to about 0.34 m, and then decreased again as the effusion rate gradually declined during the end stages of the eruption. These thickness estimates fit well with those of many feeders in Iceland and Tenerife, and with the general dyke thickness within fossil central volcanoes in Iceland.